Pengujian Trichoderma sp. Sebagai Agen Biologis Penyakit Akar Gada Plasmodiophora brassicae Wor. Pada Tanaman Sawih Hijau Brassica juncea di Kelurahan Kakaskasen Tomohon - Waroka, Tania C.; Tairas, Robert W.; Paruntu, Meisye H.B. (JURNAL ENFIT : Entomologi dan Fitopatologi, 2023)
Green mustard is one of the most marketed vegetable crops and is favored by the public because it has prospects, potential, and high enough nutrition. one of the diseases that is often found in green mustard plants is clubroot disease. Mace root disease is caused by the soil-borne pathogen Plasmodiophora brassicae Wor. is an important disease of cabbage and other cruciferae plants. Trichoderma sp. is an antagonistic fungal species commonly found in soil, especially in organic soil and is often used in biological control, both against soil-borne or rhizosphere pathogens and phyllosphere pathogens.This research was conducted from June to September 2022. From the results of the study showed that the results of the analysis of the attack of clubroot disease on the soil surface did not show any difference, but the attack of clubroot disease in the root showed a difference, namely from the results of the analysis showed that the treatment of Trichoderma sp. 107 was the most effective treatment in controlling clubroot disease Plasmodiophora brassicae Wor. on mustard greens Brassica juncea in Kakaskasen Village Tomohon. Keywords: Brassica juncea, Plasmodiophora brassicae, Trichoderma sp